Application of co-composted farm manure and biochar increased the wheat growth and decreased cadmium accumulation in plants under different water regimes. (May 2020) - Bashir, Arooj; Rizwan, Muhammad; Zia ur Rehman, Muhammad; Zubair, Muhammad; Riaz, Muhammad; Qayyum, Muhammad Farooq; Alharby, Hesham F.; Bamagoos, Atif A.; Ali, Shafaqat
Abstract: Toxic trace element pollution in the agricultural soils may negatively affect the plant growth. This study mainly focused on investigating the impact of co-composted biochar and farmyard manure (FYM) on wheat growth and cadmium (Cd) accumulation by plants. The different ratios of FYM and biochar were composted for two and half months and mixed in Cd-contaminated soil at a rate of 2% w/w of each treatment. After this, wheat seeds were sown in the soil at normal soil moisture (70% of soil water holding capacity (WHC)) level. After 50-day of sowing, both normal and drought stress (35% WHC) levels were applied and plants were harvested at 122 days after seed sowing. The results depicted that Cd and drought alone depressed the wheat growth, elevated the oxidative stress and Cd contents in wheat tissues. However, application of co-composted treatments increased the growth, yield, chlorophyll contents and minimized the oxidative stress in the leaves along with the reduction of Cd concentrations in wheat tissues mainly in grains. The amendments enhanced the post-harvest soil pH and minimized the soil bioavailable Cd. The increasing ratios of biochar in the compost were most effective in improving the growth and alleviating Cd toxicity and its concentration in grains. Overall, co-composted biochar and FYM might be suitable for reducing Cd in grains, but the field studies in different soils and plants are required to further explore the effects of these amendments before final recommendations. Graphical abstract: Image 1 Highlights: Co-composted FYM and biochar increased the wheat growth and yield. Co-composted FYM and biochar increased the photosynthesis of wheat. Co-composted FYM and biochar could mitigate the oxidative stress in leaves. The increasing ratios of biochar in compost were effective in decreasing Cd in grains. Increasing ratio of biochar in compost linearly decreased soil available Cd.